Democratic Republic of the Congo : Enhanced Initiative for Heavily Indebted Poor Countries-Decision Point Document. (IMF Staff Country Reports; Country Report, 2003)
This paper presents an assessment of the Democratic Republic of the Congo's eligibility for assistance under the enhanced initiative for heavily indebted poor countries. The country has made remarkable progress in consolidating the peace process, stabilizing the economic situation, and creating the conditions for sustainable economic growth and poverty reduction. The analysis supporting the poverty reduction strategy finds that structural constraints prevent the Democratic Republic of the Congo from achieving the international goal of reducing absolute poverty and meeting the goal for absolute poverty reduction.